Influences of weight loss on monocytes and T-cell subpopulations in male judo athletes - Shimizu, K.; Aizawa, K.; Suzuki, N.; Masuchi, K.; Okada, H.; Akimoto, T.; Mesaki, N.; Kono, I.; Akama, T. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine weight loss effects on immune function in judo athletes. Six elite male Japanese judo athletes (20.3 ± 0.4 years) were enrolled in this study. They completed usual weight loss programs during 2 weeks preceding an actual competition. Subjects noted the appearance of upper-respiratory tract infection (URTI) symptoms during the study period. Blood samples were obtained at 40 (baseline period: BL) and 3 (weight loss period: WL) days before and 1 day after the competition (AC). The CD3+, CD4+, CD8+, CD56+CD3-, CD28+CD4+, CD28+CD8+, and Toll-like-receptor-4+ (TLR-4) CD14+ cells were counted by using flow cytometer analysis. The 6 subjects reported 1 headache, 3 runny nose conditions, and 1 coughing instance during the WL. The CD3+, CD4+, CD8+, and CD28+CD4+ cell counts were significantly lower at WL than at BL (p = 0.05); they reverted to the baseline value at AC. The TLR-4+CD14+ cells were significantly fewer at WL (p = 0.05); they remained fewer than they had been at BL, even at AC. These results suggest that 2 weeks of weight loss before a competition can impair cell-mediated immune function and induce high susceptibility to URTI in judo athletes. Coaches, support staff, and athletes should monitor athletes' weight loss, hydration status, appearance of URTI symptoms, and immunocompetence such as lymphocytes and monocytes to prevent the physical condition from becoming worse.